Standardization for automotive exhaust pollution: Some issues in Indian perspective - Mohan D.; Agrawal A.K.; Singh R.S. (My University, 2025)
Important parameters affecting quality of emission from automobiles are vehicular technology, fuel type and quality, inspection and maintenance of in-use vehicles, and road and traffic conditions. The quality also varies with the type of engine, and load and speed at which they run. Prescribed standards are supposed to take care of all these possibilities. Different automobile engines emit the maximum amount of specified pollutants at varying driving conditions that may be different from corresponding test conditions defined in corresponding driving cycles. Further, the intake air, having significant concentrations of the pollutants and relative deficiency of oxygen particularly in highly polluted urban areas, may also yield test results showing even non-polluting vehicles as polluting. In addition, various shortcomings in the system of issuing the Pollution Under Control (PUC) certificate by authorized certification agencies, may aggravate air pollution problem. This paper critically examines various issues related to automobile exhaust pollution control standards, PUC norms and inconsistencies in driving cycles with a view to help emerge more realistic and effective standards in near future.